Black hole attack prevention scheme using a blockchain-block approach in SDN-enabled WSN. (8th May 2021) - Karakoç, Emre; Çeken, Celal
The success of software-defined networking (SDN) technology in the wired environment has accelerated the research on the deployment of SDN in wireless sensor networks (WSN). Since the wireless environment has a shared nature, it is more vulnerable to routing attacks. Most of the existing security protocols cannot be implemented for WSN, as the wireless environment has physical restrictions and the nodes in the network have limited energy, processing capacity, and memory. This paper investigates the possible threats in SDN-enabled WSN and analyses the black hole attack in detail. In the paper, we have also proposed a novel lightweight security model that exploits the blockchain-block approach to be able to protect the flow table in each node, which is the main target of possible routing attacks. We have generated an unchangeable fingerprint called the signature token for the flow entries with a secret key belonging to each node. Thanks to this token, not only have the flow entries been secured against tampering but also data packets have been transmitted securely along the path and secured against replay attacks and man-in-the-middle attacks. The results show that the proposed security model can be a promising solution for securing SDN-enabled WSN structures.